Single-cell and spatial transcriptomics reveal transplant-associated T cells and myeloid cells in human liver transplantation - Zhou, Tianyang; Guo, Kun; Dong, Chengyong; Wang, Yuhui; Gao, Jiajun; Xu, Zhenyu; Shi, Zhaoyun; Jiao, Zhiqi; Xia, Cong; Hu, Ke; Gao, Zhenming (Frontiers in Immunology, 2026)
BackgroundLiver transplantation is the only effective way for end-stage liver disease. Rejection remains the leading cause of graft failure. The dynamic changes of intrahepatic immune cells involved in rejection are not completely understood.MethodsWe integrated single-cell RNA sequencing and spatial transcriptomics (ST) to analyze graft tissues from multiple stages of human liver transplantation. ST enabled high-resolution mapping of immune cell states and spatial distribution within liver grafts.ResultsWe identified several transplantation-associated T cell (taT) subsets, including CD4+ effector-like T cells (Teff_like), CD8+ precursor exhausted T cells (Tpex), and CD8+ transitional effector-like T cells (tTeff_like). The CD4+ Teff_like subset highly expressed chemokines such as CCL3. The CD8+ tTeff_like subset represented an intermediate state transitioning from the CD8+ Tpex subset toward terminal exhaustion and was enriched in the immune activity pathway. Monocyte_PPARG, enriched in the rejection group, may be recruited by CD4+ Teff_like via the MIF-(CD74+CD44) pathway and subsequently promote CD8+ Tpex to tTeff_like differentiation through the ICAM1-LFA1 pathway. ST suggested that these immune subsets dominated the rejecting liver grafts.ConclusionThese findings highlight the potential roles and spatial distribution of taT subsets in rejecting liver grafts, providing insights into local immune regulation and the development of targeted therapeutic strategies.